Surface engineered amphiphilic carbon dots: solvatochromic behavior and applicability as a molecular probe. Issue 5 (19th January 2021) - Pandit, Subrata; Mondal, Sudipta; De, Mrinmoy
Abstract : Synthesis of core–shell amphiphilic carbon dots under very mild conditions using various positional isomers of phenylene diamine and their application in the detection of biomolecular surfaces. Abstract : Carbon dots (C-dots) have attracted great attention in the fields of nanotechnology and bioengineering owing to their unique and tunable optical properties with excellent photoluminescence characteristics. Herein, we have engineered amphiphilic C-dots (AC-dots) using positional isomers of diamino benzene with citric acid under mild microwave irradiation to minimize any background reactions. The optical properties changed from excitation-dependent to excitation-independent depending on the isomer used. This unique optical property of the AC-dots was studied in the presence of various solvents and we extensively inspected the AC-dot–solvent interactions. The intensity of the emission wavelength varied with solvent polarity and showed a linear relationship. Furthermore, we extended this property to investigate the molecular environment in biomolecular systems such as proteins. Interestingly, we found that, in the presence of various proteins, the emission intensity was enhanced, quenched or remained unchanged depending on the nature of the protein surface. The mode of interaction between AC-dots and protein was determined using temperature-dependent fluorescence spectroscopy. This study could provide vital information about the surfaces of proteins and the potential application of C-Dots as a fluorescent probe to detect biological molecules and environments.